Parents' lived experience of providing kangaroo care to their preterm infants - Angela Leonard; Pat Mayers (AOSIS, 2008)
Premature and low birthweight infants pose particular challenges to health services in South Africa. While there is good evidence to demonstrate the benefits of kangaroo care in low birthweight infants, limited research has been conducted locally on the experiences of parents who provide kangaroo care to their preterm infants. This phenomenological study explores the lived experience of parents who provided their preterm infants with kangaroo care at a tertiary-level maternity centre in the Western Cape. In-depth interviews were conducted with six parents: four mothers and two fathers. Data was analysed using an adaptation of the approaches described by Colaizzi (1978:48-71) and Hycner (1985:280-294). To ensure trustworthiness, the trustworthiness criteria described by Guba and Lincoln (1989:242-243) were applied. Kangaroo care is a phased process, each phase bringing a unique set of experiences. The eight themes that emerged are described: unforeseen, unprepared and uncertain - the experience of birth; anxiety and barriers; an intimate connection; adjustments, roles and responsibilities; measuring success; a network of encouragement and support; living-in challenges; and living with the infant outside of hospital. Challenges facing health care providers are described and recommendations for information about kangaroo care and support for parents are made. Opsomming Vroeggebore babas en babas met 'n lae geboortegewig stel besondere uitdagings vir Suid-Afrikaanse gesondhiedsdienste. Daar bestaan goeie bewyse dat die kangaroesorgmetode voordelig is vir babas met 'n laegeboortegewig, dog is minimale plaaslike navorsing gedoen oor die ondervindinge van ouers wat hierdie metode gebruik om vir hul vroeggebore babas te sorg. Hierdie fenomenologiese studie verken die geleefde ervaringe van ouers wat vir hulle vroeggebore babas deur middel van die kangaroesorgmetode in 'n tersiêre kraamsentrum in die Weskaap gesorg het. Data is ingesamel deur in-diepte onderhoude met ses ouers te voer: vier moeders and twee vaders van vroeggebore babas. Data is ontleed volgens 'n verwerking van die metodes soos deur Colaizzi (1978:48-71) en Hycner (1985:280-294) beskryf. Om betroubaarheid te verseker, is die betroubaarheidskriteria van Guba en Lincoln (1989:242-243) toegepas. Kangaroesorg is 'n geleidelike proses; elke fase lei tot 'n unieke stel ondervindinge. Agt temas is uit die data geïdentifiseer: Onverwags, onvoorbereid en onseker - die geboorte-ervaring; angstigheid and hindernisse; 'n intieme verband; aanpassings, rolle en verantwoordelikhede; die meting van sukses; 'n netwerk van aanmoediging en ondersteuning; die uitdagings van binne die hospitaal leef; saamleef met die baba buite die hospital. Uitdagings wat gesondheidspersonnel te voorstaan kom en aanbevelings oor inligting met betrekking tot kangaroesorg en ondersteuning aan ouers word voorgestel.